2020
DOI: 10.1148/ryct.2020200004
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Mitral Valve Regurgitation from 4D Flow MRI Using Semiautomated Flow Tracking

Abstract: To compare the accuracy of semiautomated flow tracking with that of semiautomated valve tracking in the quantification of mitral valve (MV) regurgitation from clinical four-dimensional (4D) flow MRI data obtained in patients with mild, moderate, or severe MV regurgitation. Materials and Methods: The 4D flow MRI data were retrospectively collected from 30 patients (21 men; mean age, 61 years 6 10 [standard deviation]) who underwent 4D flow MRI from 2006 to 2016. Ten patients had mild MV regurgitation, nine had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 31 publications
0
20
0
1
Order By: Relevance
“…A recent in vivo study that compared the RVol quantified at the valve (i.e., valve tracking) to that quantified at 1-2 cm above the valve (i.e., flow tacking) reported similar results. 15 The former approach underestimated RVol, whereas the latter approach produced higher RVol with better internal flow consistency (aortic valve net flow = mitral valve net flow) and better agreement with the CMR indirect method. A number of prior studies have also demonstrated a strong correlation between flow tracking based RVol with the CMR indirect method.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…A recent in vivo study that compared the RVol quantified at the valve (i.e., valve tracking) to that quantified at 1-2 cm above the valve (i.e., flow tacking) reported similar results. 15 The former approach underestimated RVol, whereas the latter approach produced higher RVol with better internal flow consistency (aortic valve net flow = mitral valve net flow) and better agreement with the CMR indirect method. A number of prior studies have also demonstrated a strong correlation between flow tracking based RVol with the CMR indirect method.…”
Section: Discussionmentioning
confidence: 83%
“…10 This technique can acquire 3-directional velocity vectors in the threedimensional (3D) left atrium space over time, enabling retrospective positioning of flow measurement planes that follow the movement of the mitral valve [11][12][13][14][15] or the regurgitant jet. [15][16][17][18] Prior studies used retrospective valve/jet tracking techniques to quantify RVol directly from 4D flow MRI and reported a strong correlation with the CMR indirect method 15,16,18 and 3D echocardiographic method. 19 However, because of the lack of a gold standard in MR assessment, MR flow quantification accuracy using 4D flow MRI is still questionable.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, but not in the cited studies, this may have been caused by a difference in frame rate: following the normal clinical scan protocol, 2D flow MRI was reconstructed into 40 cardiac frames as opposed to 30 in the 4D flow MRI acquisitions. In addition, the lower spatial resolutions of 4D flow MRI (2.5 Â 2.5 Â 2. differences in LVSV quantification, 15 whereas 4D flow MRIbased valve tracking analysis has demonstrated good interobserver agreement. 9 Furthermore, stroke volume quantification by a combination of short-axis bSSFP volumetry and 2D flow MRI is sensitive to physiological variability and the patient's ability to hold their breath.…”
Section: Discussionmentioning
confidence: 99%
“… 26 The 2D cine and 4D flow MRI images were aligned, and contours were drawn to measure the blood flow across all four heart valves. As parameters of interest, forward flow volume [ml], backward flow volume [ml], regurgitation fraction [ ], 27 and velocity rate [cm/s] (mean of the contour per time point) per valve were chosen. Moreover, backward flow volumes and regurgitation fraction were compared of a mixed subgroup n 2 containing only valves diagnosed with insufficiency.…”
Section: Methodsmentioning
confidence: 99%